Organizational Justice from the Perspective of Potential Applicants - Anip Bustaman1, Hasnun; Malek A. Tambi, Abdul (International Journal of Engineering and Technology, 2018)
This paper reviews the recent advancement of organizational justice influencing the people from outside organizations, which has been gaining keen attention from scholars lately. Precisely, this paper aims to construe organizational justice with a greater emphasis on the potential applicant attraction. The discussion involved the elementary of four justices encompassing procedural justice, distributive justice, interpersonal justice and informational justice in the eye of potential applicant. Finally, this paper enlarged the conceptuality of study by providing some arguments of appropriate methodology for empirical testing.Â Â